Improved cancer coping from a web‐based intervention for prostate cancer survivors: A randomized controlled trial. Issue 9 (28th April 2021) - Tagai, Erin K.; Miller, Suzanne M.; Hudson, Shawna V.; Diefenbach, Michael A.; Handorf, Elizabeth; Bator, Alicja; Marziliano, Allison; Kutikov, Alexander; Hall, Simon J.; Vira, Manish; Schwartz, Michael; Kim, Issac Yi; et al.
Abstract: Objectives: Prostate cancer (PCa) survivors report poor physical functioning alongside negative psychological outcomes as they cope with treatment side effects and practical concerns after treatment completion. This study evaluated PROGRESS, a web‐based intervention designed to improve adaptive coping among PCa survivors. Methods: Localized PCa patients ( N = 431) within one year of treatment completion were randomized to receive educational booklets or PROGRESS + educational booklets. Surveys completed at baseline, 1‐, 3‐, and 6‐months assessed patient characteristics; functional quality of life and coping ( primary outcomes ); and psychosocial outcomes (e.g., self‐efficacy, marital communication; secondary outcomes ). Intent‐to‐treat and as‐treated analyses were completed to assess change in outcomes from baseline to 6 months using linear mixed effects regression models. Results: In the intent‐to‐treat analyses, participants randomized to the intervention group had improved diversion coping (i.e., healthy redirection of worrying thoughts about their cancer), but more difficulties in marital communication ( ps < 0.05). However, PROGRESS usage was low among those randomized to the intervention group (38.7%). The as‐treated analyses found PROGRESS users reported fewer practical concerns but had worse positive coping compared to PROGRESS non‐users ( ps < 0.05). Conclusions: The findings suggest PROGRESS may improve certain aspects of adaptive coping among PCa survivors that use the website, but does not adequately address the remaining coping and psychosocial domains. Additional research is needed to better understand the gaps in intervention delivery contributing to low engagement and poor improvement across all domains of functional quality of life and adaptive coping.